Disentangling Taxation Right Rules in Business Taxation: Tracing the Work of International Organisations - Allen, Christina (2022)
The international effort to coordinate tax rules across nations began nearly a century ago, originally aimed at eliminating double taxation. The effort was expanded to tax business profits on a more consistent basis worldwide. However, these rules have changed over time without a solid foundation of clear and coherent principles, causing schisms in dealing with multiple taxpaying entities and intragroup transactions. While the Organisation for Economic Co‑operation and Development (OECD) has a large‑scale initiative underway to reset international tax norms to prevent base erosion and profit shifting, the initiative is unlikely to settle the tax challenges of the 21st century since it is likely to create further conceptual distortions. This article tracks the historical development and evolution of international tax rules related to business profits set out by the League of Nations, the Organisation for European Economic Co‑operation (OEEC), the United Nations (UN) and the OECD. The fragmented approach to a narrow set of problems demonstrates that cooperative international tax settlement is far from over. A better alternative for business taxation would begin with removal of the concept of corporate residence, followed by reconceptualisation of base allocation rules to determine the jurisdictions to tax.